Application of Regional Cultural Elements in Urban Complex-Illustrated by Guizhou, China. Issue 3 (1st September 2016) - Mingman, Chen; Hong, Ren; Weiguang, Cai; Xiaohui, Li; Pengyu, Ren; Lee, Deson
Abstract : Along with the acceleration of Chinese urbanization, urban history degrades at a rapid rate, and development follows formalism. Based on architectural typology, this study introduces a methodology of concept mapping and discusses the urban complex design method from a perspective of regional cultural elements. The theoretical analysis shows that concept mapping represents an integrated solution that incorporates regional cultural elements into architectural planning. Through the concept mapping method, it not only protects the physical environment, but also strengthens modern urban residents' psychological sense of belonging to their own living space. Meanwhile, distinct regional cultural elements can be efficiently combined in the overall layout, monomer building design, building details design, and landscape design of urban complex by using different architectural design methods. This design method is validated using an actual case in Guizhou. Therefore, it forms a complete set of design method with a three-step framework, namely positioning cultural areas, summarizing regional cultural elements, and selecting the mapping method and combination mode.